Toward an integrated understanding of the youth sport system - Dorsch, T. E.; Smith, A. L.; Blazo, J. A.; Coakley, J.; Côté, J; Wagstaff, C. R.; Warner, S.; King, M. Q. (Research Quarterly for Exercise and Sport, 2022)
The aim of the present article is to outline a heuristic model that facilitates movement toward an integrated understanding of the youth sport system. We define the youth sport system as the set of interdependent persons and contexts that influence and are influenced by an athlete in youth sport. Our model builds directly from a systems perspective, and its tenets of holism, feedback loops, and roles. Specifically, we argue that the persons and contexts that surround an athlete in youth sport should be examined collectively, self-correct over time, and take on certain functions that are negotiated over time. The model extends past contributions toward integration by outlining how proximal and distal processes within youth sport can be studied in a more unified way. Looking forward, research designed to capture the nuanced ways persons and contexts influence and are influenced by one another in youth sport will be best positioned to impact theory and practice in meaningful ways.